2018
DOI: 10.1108/bfj-10-2017-0554
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and young adults’ perceptions of secondary school food education in Australia

Abstract: Purpose Secondary school food education provides students with opportunities to build lifelong healthy dietary practices. A number of stakeholder groups are important for the success of this form of education. Accordingly, the purpose of this paper is to examine young adults’ and parents’ opinions of secondary school food education. Design/methodology/approach An online survey was administered to 1,086 respondents drawn from a commercial research panel. Findings In total, 50-60 per cent of all respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(88 reference statements)
2
8
0
Order By: Relevance
“…Building on this, middle (years 9 and 10) and upper secondary grades (years 11 and 12) might be provided with more applied and critical food literacy knowledge and skills [ 3 , 9 ] such as food ethics, food regulation, and social equity in food distribution. Consistent with the previous published findings of the authors [ 42 , 49 ] and a recent Australian study that explored teachers’ opinions of school food literacy education [ 29 ], the respondents indicated that making the food literacy subjects compulsory would help to raise the status and recognition of these subjects in schools.…”
Section: Discussionsupporting
confidence: 85%
“…Building on this, middle (years 9 and 10) and upper secondary grades (years 11 and 12) might be provided with more applied and critical food literacy knowledge and skills [ 3 , 9 ] such as food ethics, food regulation, and social equity in food distribution. Consistent with the previous published findings of the authors [ 42 , 49 ] and a recent Australian study that explored teachers’ opinions of school food literacy education [ 29 ], the respondents indicated that making the food literacy subjects compulsory would help to raise the status and recognition of these subjects in schools.…”
Section: Discussionsupporting
confidence: 85%
“…Findings from the present study suggest the majority of young males are in favor of mandatory food skills education. Similar views have been reported among young adults (Nanayakkara et al, 2018;Worsley, 2006), and by the public at large (Pendergast et al, 2011;Wolfson et al, 2017). Although the majority (n 5 37) of the participants in this study supported mandatory education, only a third (n 5 16) deemed schools responsible for teaching food skills.…”
Section: Discussionsupporting
confidence: 80%
“…Food skills education in schools remains a predominantly female subject (Nanayakkara et al, 2018), a viewpoint shared by participants in the present study. In one Canadian province, the female to male ratio for home economics food and nutrition courses across grades 7 to 12 averaged 1.32 (Slater, 2013).…”
Section: Discussionmentioning
confidence: 77%
“…The specificity of this software is analysis of "the meanings within passages of text by extracting the main concepts and ideas" instead of applying word frequencies (Tseng et al, 2015, p. 350). The unsupervised seeding option was set (Nanayakkara et al, 2018), validated by previous studies (Smith and Humphreys, 2006), and the software automatically scanned textual data producing descriptors and associating them to build themes. Leximancer labelled the emerging themes in light of the most cooccurring descriptors.…”
Section: Discussionmentioning
confidence: 99%
“…, 2015, p. 350). The unsupervised seeding option was set (Nanayakkara et al. , 2018), validated by previous studies (Smith and Humphreys, 2006), and the software automatically scanned textual data producing descriptors and associating them to build themes.…”
Section: Methodsmentioning
confidence: 99%